Education for a New Era, Executive Summary Design and Implementation of K-12 Education Reform in Qatar - Brewer, Dominic J. (RAND Corporation, 2007)
Presents an overview of Phase I (2001-2004) of Qatar's bold K-12 education reform initiative, Education for a New Era, based on RAND's experiences in this ambitious, multi-participant effort. RAND examined Qatar's existing education system, recommended options for building a world-class system, and supported implementation of the chosen option, which is based on internationally benchmarked curriculum standards and parental choice of schools.